2003
DOI: 10.1238/physica.regular.068a00394
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dust Kinetic Alfvén Waves in Warm Dusty Plasmas

Abstract: Retaining the complete dust nonlinearity, dust-kinetic Alfvén solitary waves have been investigated in warm, small but finite-β dusty plasmas. The nonlinear energy integral equation describing the warm dust-kinetic Alfvén solitary waves is derived. The effects of finite dust temperature on the dust-kinetic Alfvén solitary waves are studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[35,36]). Using (15) and (16) into equation (14), one obtains the nonlinear dispersion relation [35] …”
Section: Derivation Of the Nonlinear Dispersion Relationmentioning
confidence: 99%
“…[35,36]). Using (15) and (16) into equation (14), one obtains the nonlinear dispersion relation [35] …”
Section: Derivation Of the Nonlinear Dispersion Relationmentioning
confidence: 99%
“…They found that the increase of b plays a destructive role for solitons formed. Jukui [28] studied the effect of the finite dust temperature in dust kinetic Alfvén waves. Gogoi and Devi [29] investigated arbitrary amplitude double layers in warm plasma considering Boltzmann distributed ions and electrons and obtained exact analytical expression for the energy integral.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies [24][25][26][27][28][29][30][31] do not include the effect of ion inertia, consider finite …”
Section: Introductionmentioning
confidence: 99%